Chapter The politics of washoku: Japan's gastronationalism and gastrodiplomacy - FARINA, FELICE (Studi e saggi, 2021)
In this paper, we will explore the political construction of washoku by analyzing Japan's recent strategy of gastronationalism and gastrodiplomacy. We will argue that the definition of washoku, as inscribed in the UNESCO's International Cultural Heritage List in 2013, is the result of a process of invention of tradition whose aim is to homogenize and preserve national identity and project this identity abroad. While emphasizing the role of food as an essential element of national identity, we will also show that the promotion of washoku is also motivated by the need to address several issues of broader domestic politics. Starting from the assumption that Japan's low food self-sufficiency rate could be improved only by increasing the demand for Japanese food, the government implemented a strategy of promotion of washoku at home (gastronationalism) and abroad (gastrodiplomacy) in order to increase both the domestic consumption of traditional food and the export of agrifood products.